2021
DOI: 10.1111/jcmm.16684
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Janus Kinase 1 synergizes docetaxel sensitivity in prostate cancer cells

Abstract: Prostate cancer (PCa) is the second most common malignancy and is the fifth leading cause of cancer mortality among men globally. Docetaxel‐based therapy remains the first‐line treatment for metastatic castration‐resistant prostate cancer. However, dose‐limiting toxicity including neutropenia, myelosuppression and neurotoxicity is the major reason for docetaxel dose reductions and fewer cycles administered, despite a recent study showing a clear survival benefit with increased total number of docetaxel cycles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 88 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…Targeting the JAK/STAT pathway can also reverse drug resistance to chemotherapy or TKIs 84–87 . For instance, inhibition of JAK1 in prostate cancer cells enhanced sensitivity of the first‐line chemotherapeutic drug, docetaxel 87 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Targeting the JAK/STAT pathway can also reverse drug resistance to chemotherapy or TKIs 84–87 . For instance, inhibition of JAK1 in prostate cancer cells enhanced sensitivity of the first‐line chemotherapeutic drug, docetaxel 87 .…”
Section: Resultsmentioning
confidence: 99%
“…82 Targeting the JAK/STAT pathway can also reverse drug resistance to chemotherapy or TKIs. [84][85][86][87] For instance, inhibition of JAK1 in prostate cancer cells enhanced sensitivity of the first-line chemotherapeutic drug, docetaxel. 87 In EGFR-mutant lung adenocarcinoma, inhibition of JAK2 causes EGFR to detach from its negative regulator SOCS5, resulting in increased reexpression of tumor cell EGFR, thus, EGFR inhibitors such as erlotinib or gefitinib regain efficacy.…”
Section: The Jak/stat Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Only one gene (homeobox A10 (HOXA10) (NM_018951)), which was upregulated by two-fold ( p < 0.05), belonged to two gene groups: the transcriptional factor and epigenetically regulated genes ( Table 6 ). The Search Tool for the Retrieval of Interacting Genes/Proteins (STRING Consortium 2022) (Version 11.5) ( (accessed on 20 May 2022)) software was used to predict the protein–protein interaction (PIP) in a virtual situation to show the vital interactions as well as possible signaling pathways that these dysregulated genes affect [ 25 ] ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Baricitinib was also approved as a treatment for COVID-19 in 2020 by the EUA and in 2022 by the FDA ( Shawky et al, 2022 ). The efficacy of baricitinib as a cancer therapy has rarely been considered so far, although one has study reported that baricitinib did not induce apoptosis of T-ALL ( Akahane et al, 2017 ), whereas synergistic effects for its combination with docetaxel were observed in androgen-receptor-negative prostate cancer cells ( Nalairndran et al, 2021 ). Potential effects on the risk of tumorigenesis have also been evaluated; one study reported that the malignancy rate in RA patients treated with baricitinib was high but not significantly different from that of the general population or of patients treated with TNF inhibitors ( Uchida et al, 2023 ).…”
Section: Potential Anti-tumor Role Of Jak Inhibitor Drugs Approved Fo...mentioning
confidence: 99%